Діагностика ізоляції силових кабелів із застосуванням методів діелектричної спектроскопії: огляд фізичних основ та особливостей практичного застосування - Костюков, Іван Олександрович; Борисенко, Анатолій Миколайович; Литвиненко, Світлана Анатоліївна; Ільчакова, Яна Михайлівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Стаття присвячена огляду фізичних основ діелектричної спектроскопії паперової та поліетиленової ізоляції силових кабелів в часовій та частотній областях. Наведено аналіз основних факторів, що впливають на частотну залежність тангенса кута діелектричних втрат та комплексної діелектричної проникності ізоляції. Наведено перелік та коротку характеристику основних типів реакції поліетиленової ізоляції на рівні та частоту прикладеної напруги в залежності від ступеню її зволоження та розвитку водних каналів. Наведено зв'язок між параметрами діелектричної спектроскопії в часовій та частотній областях.

The article provides an overview of the physical foundations and features of the application of diagnostic methods for the insulation of power cables using dielectric spectroscopy methods in the frequency and time domains. The relationship between the depolarization currents and the frequency spectrum of the complex dielectric constant is shown. An analysis of the factors determining the frequency dependence of the tangent angle of dielectric losses of paper and polyethylene insulation of power cables is given. The main types of reaction of dielectric materials with different levels of develop-ment of water channels at the level and frequency of the applied voltage are listed. According to the results of the analysis, it is shown that for high-voltage measurements, one of the factors that complicates the diagnosis of the insulation of power cables by analyzing the frequency dependences of the capacitance and the tangent of the dielectric loss angle is the distortion of the sinusoidal current through the dielectric due to the nonlinear dependence of the complex dielectric constant on the level of the applied voltage. A comparative analysis of dielectric spectroscopy methods in the frequency domain, involving high-voltage and low-voltage measurements of the complex dielectric constant, was carried out. The correlation between the tangent of the dielectric loss angle of paper insulation and its mechanical characteristics is shown.
Diagnostics of power cable insulation by using the methods of dielectric spectroscopy: overview of physical basis and features of practical application
Keywords: діагностика ізоляції; комплексна діелектрична проникність; діелектричні втрати; поляризація діелектриків; електропровідність діелектриків; insulation diagnostics; complex dielectric permittivity; dielectric losses; polarization of dielectrics; electrical conductivity of dielectrics